Effect of Seed Loading and Temperature of Seeding on Carbamazepine-Saccharin Co-Crystal - K. A., Mohammad; Syarifah, Abd Rahim; M. R., Abu Bakar (Informatics Publishing Limited, 2017)
Objectives: In pharmaceutical industries, the properties of desired final crystal can be modified by seeding process. Seeding activities depend on seed loading, seed size, seed quality and the temperature of supersaturated solution at the time of seed addition. The effect of amount of seed and temperature of seeding on crystallisation and size distribution of carbamazepine-saccharin (CBZ-SAC) co-crystals have been investigated. Methods/Statistical Analysis: 0.5, 1.0 and 1.5 wt% seeds of constant size were added to the metastable zone width region during cooling crystallisation at seeding temperatures of 38.45, 40.35, 42.25, 44.15 and 46.05 oC. Findings: During the crystallisation process of CBZ-SAC co-crystal, nucleation occurred faster when seeding is close to the super solubility curve which is at the highest supersaturation. Crystal size distribution (CSD) results showed more fine particles formed at 38.45oC seed temperature. On the other hand, nucleation occurred slower when seeding is close to the solubility curve, which is at low supersaturation and therefore resulted in less number of fine particles formed. Application: Nucleation of CBZ-SAC co-crystals can be controlled easily by seeding, in which the addition of seed expedites the crystallisation process by providing the surface area for crystals to grow. The size and characteristic of the desired crystal can be adjusted via seeding application.